Exploring environmental and biological drivers of cetacean occurrence in the cross-border region of the Malin Shelf using data from a European fishery survey - Pommier, Morgane; O’Donnell, Ciaran; Barile, Cynthia; McGill, Ross; Berrow, Simon; O’Brien, Joanne (Frontiers in Marine Science, 2023)
Irish and Scottish waters are important habitats for cetaceans in Europe. Yet, little data is available for the region of the Malin Shelf, north of Ireland. Despite a rich species diversity, relative cetacean abundance appears low compared to hotspots documented west of Scotland and Ireland. Whether this perceived low prevalence accurately portrays an ecological discontinuity or arises from a lack of published results and low survey effort in that transborder area remains unclear. Here, we used sighting records from a multi-disciplinary fisheries survey, the Western European Shelf Pelagic Acoustic Survey (WESPAS), to explore cetacean habitat preferences over the Malin and Hebridean shelves. Northern minke whale and common dolphin occurrence was modelled within a Bayesian Additive Regression Trees (BART) framework, against selected environmental and biological variables. No correlation was observed between cetacean presence and in-situ prey biomass. Minke whales distribution was better explained by oceanography, notably proxies for frontal activity, and primary productivity. Common dolphins similarly showed preferences for shelf waters within 5-25km of fronts, but also affinities for fine substrates. Favourable habitats identified by the models were consistent with literature around the Hebrides and shed light on potentially important areas along the Islay front and north of Donegal, so far unreported due to data deficiency. Results will contribute towards informing future monitoring, strategic management and conservation efforts in this cross-border region.